The Relationship Between Technical, Social, Economic, Financial and Management Factors on the Prospects for Development of Integrated Beef Cattle and Cashew Farming in Muna Regency - Rizal, Abdul; Ginting, Nina Maksimiliana; Redu, Silas T; Suriani, Wa Ode; Simatupang, David Oscar; Maga, La (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2024)
The aim of this research is to relate technical, social, economic, financial and management factors to the prospects for developing integrated beef cattle and cashew farming in Muna Regency. This research was conducted in Muna Regency, Southeast Sulawesi Province. The location was determined purposively with the consideration that Muna Regency is one of the areas that has the largest cattle population and has cashew plantation land. The population in this research was 100. The data collected in this research were primary data and secondary data. The data analysis used is Pearson Correlation analysis at α = 0.05. The research results showed that the technical aspect had a correlation coefficient of 0.569 with a confidence level of 99%. Economic aspect 0.504 with a confidence level of 99%. Social and financial aspects are 0.278 and 0.352 respectively with a confidence level of 95% and 99%. Management aspect 0.587 with a confidence level of 99%.